Prevalence and associated risk factors of hypertension in rural and urban areas of Punjab: A cross-sectional study - Jasvinder Singh; Syed A. Iqbal; Tareq I. Mohammed; Prithvi Radhavan; Shreya Rajpal; Sahini Gajula; Shree Rath (Journal of Family Medicine and Primary Care)
Context: Hypertension is a growing concern worldwide, particularly in developing countries. In India, it significantly contributes to morbidity and mortality. Various states have reported an increasing incidence of hypertension, underscoring the need to assess its prevalence and associated risk factors. Aims: This study aimed to evaluate the prevalence of hypertension in Punjab, compare urban and rural areas, and identify the associated risk factors. Settings and Design: A community-based cross-sectional study was conducted across Ludhiana, Punjab, involving three urban areas and three villages. Methods and Materials: Residents aged 20 years and older were selected, and their blood pressure was measured according to JNC-7 guidelines. Other demographic details and personal histories, including alcohol consumption and hypercholesterolemia, were documented for each participant. Results: The prevalence of hypertension in Ludhiana was 62%, with an equal distribution between rural and urban areas. However, fewer individuals in rural areas were aware of their hypertensive status, and the number of new cases was higher in these areas. Hypertension was notably more prevalent among males and those with lower educational backgrounds. Identified risk factors included obesity, a sedentary lifestyle, high socioeconomic status (SES), salt intake, stress levels, alcohol consumption, hypercholesterolemia, and low literacy rates, which were more prevalent in rural areas compared to urban areas. Conclusions: Our study highlights the increasing incidence of hypertension in Punjab, emphasizing that rural populations are more likely to be unaware of their condition. This finding suggests a limited reach of adequate healthcare services in these areas.